Religious service attendance and consumer financial outcomes: Evidence from a longitudinal survey - Cwynar Andrzej; Potocki Tomasz; Białowolski Piotr; Węziak-Białowolska Dorota (Economics and Business Review)
Previous literature has pointed to strong links between religion and economic outcomes. However, little is known about how individual consumers ’  religiosity is related to their financial management outcomes. Using longitudinal data from a national representative survey of households in Poland (more than 90% of believers declaring Roman Catholic religious denomination), we examine the associations between religious service attendance (RSA) and three subsequent consumer financial outcomes: savings, debt, and financial satisfaction. Social contacts, general trust, and risk tolerance have been tested to mediate these associations. The results indicate that RSA is prospectively associated with all three consumer financial outcomes: savings (positive), debt (negative), and financial satisfaction (positive). Only one mediation effect was found: the association between RSA and savings is mediated by social contacts. This implies that religiosity, as measured by RSA, is prospectively associated with financial outcomes, and social contacts have some potential to mediate the process. The channels through which religion influences financial conditions require additional research.